GAZING AT THE BODY AS A LOCUS OF COMPETENCE: IMPLICATIONS FOR LANGUAGE EDUCATION - Sugiharto, Setiono (LLT Journal: A Journal on Language and Language Teaching, 2022)
It is well-established that the notion of language competence often bandied about in English language teaching scholarship owes much of its allegiance to the Chomskyan tradition, which privileges mind over body and other materiality. Tracing this tradition to its root, one may surmise that the infamous Chomskyan competence has been the sustenance of Cartesian linguistics as the Neo-Platonic philosophical tradition known for its condemnatory arguments against body in the pursuit of knowledge. Basing on the idea of somaesthetics initially proposed by Richard Shusterman, I argue in this conceptual article that English language teaching landscape needs to embrace insights generated by current research and theorization on the pivotal role of the soma (the living body) as a source of competence in facilitating communicative practices. I will first discuss the notion of somaesthetic, and then demonstrate that research in language teaching and language acquisition scholarship (albeit limited in numbers) has long been inspired by this body philosophy. Implications for English language teaching will be offered.